Public services at the service of citizens – Case-study: cleaning services - Cliza, Marta Claudia (International Journal of Legal and Social Order, 2023)
Public services are unquestionably a pillar of society. The society develops and blooms on their importance, on the way they are organized, on their efficiency. This is why we could devote a case study to each public service that a nation, through its government representatives, organizes and operates, in order to analyze its efficiency and impact on the quality of life of its citizens. However, this article is focused on public cleaning service, as currently regulated in the legislation. The importance of public cleaning service cannot be denied, by being a comfort factor and the criterion indicating the level of civilization.